PD-1 Affects the Immunosuppressive Function of Group 2 Innate Lymphoid Cells in Human Non-Small Cell Lung Cancer - Shen, Chunyi; Liu, Chaojun; Zhang, Zhen; Ping, Yu; Shao, Jingwen; Tian, Yonggui; Yu, Weina; Qin, Guohui; Liu, Shasha; Wang, Liping; Zhang, Yi (Frontiers in Immunology, 2021)
Background There is increasing evidence that group 2 innate lymphoid cells (ILC2s) play an essential role in allergy and parasitic infection. However, the role of ILC2s in human lung cancer remains unclear. Methods ILC2s from peripheral blood mononuclear cells (PBMCs) obtained from healthy donors (HDs) and non-small cell lung cancer (NSCLC) patients, and NSCLC tumor tissues were analyzed via multicolor flow cytometry. ILC2s or CD14+ cells were sorted by fluorescence-activated cell sorting. qPCR and flow cytometry were performed to assess the gene and protein expression of the indicated molecules. M1-like and M2-like macrophages were induced from CD14+ monocytes in vitro. Results ILC2s were significantly more enriched in PBMCs and tumor tissues from NSCLC patients than in HDs. After screening for the main immune checkpoint molecules, we found that PD-1 was upregulated in ILC2s in NSCLC patients. Functionally, PD-1high ILC2s from tumor tissues expressed higher levels of IL-4 and IL-13 regarding both mRNA and protein levels than PD-1low ILC2s. Furthermore, PD-1high ILC2s robustly boosted M2-like macrophage polarization in vitro, by secreting IL-4 and IL-13, while neutralization of IL-4 and IL-13 by antibodies abrogated M2-like macrophage polarization. Conclusion ILC2s are enriched in NSCLC patients and upregulate PD-1 expression. Upregulation of PD-1 facilitates the immunosuppressive function of ILC2s. PD-1high ILC2s enhance M2-like macrophage polarization by secreting IL-4 and IL-13. PD-1 acts as a positive regulator of the immunosuppressive function of ILC2s in human NSCLC.